Implementation of Standardization Policy for Cross-Border Service Posts - Rares, Joyce Jacinta (Journal La Sociale, 2024)
Marore Island, which is part of the Sangihe Islands Regency, has for many years been a gateway and also a center for cross-border trade between the residents of the Sangihe Islands and the residents of the South Philippines. The strong inflow of goods then tends to be more "illegal trading". The Sangihe Islands Regency Government then tried to overcome this by issuing Sangihe Islands Regency Regional Regulation Number 4 of 2013 concerning the Standardization of Marore Cross-Border Service Posts. However, after more than 5 years of this policy being established, it turns out that the problems in the field have not been resolved. In fact, this cross-border trade tends to expand and shift to the capital area of the Regency, namely to the city of Tahuna and also to the sub-district of Peta. On the basis of this reality, research is carried out to find weaknesses and shortcomings in the implementation of this policy. The goal is to produce relevant and appropriate policy designs to overcome this problem. This study is designed using a descriptive qualitative method and uses the policy implementation theory from Jones (1984) which states that policy implementation is related to aspects of organization, interpretation, and application. The output of this research is aimed at academic interests and practical interests. The academic interest is to obtain IPR and the practical interest is to be used as a concrete academic proposal for the re-design of the Sangihe Islands Regency Regional Regulation Number 4 of the Year concerning the Standardization of the Marore Cross-Border Service Post.